Hemidysgeusia, phantosmia and respiratory arrest: a case of CLIPPERS. Issue 5 (30th May 2019) - Nguyen, Peter Baoviet; Prentice, David; Brazel, Robert; Leong, Wai Kuen
Abstract : A 56-year-old man presented with a relapse of likely chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS) after a reduction of steroid dose. MRI demonstrated new perivascular FLuid-Attenuated Inversion Recovery (FLAIR) signal hyperintensity involving the dorsal pontomedullary junction and progressing inferiorly into the dorsal medulla oblongata. His admission to hospital was complicated by a respiratory arrest.